Critical Analysis of Nursing Interventions in Public Health: Addressing Socioeconomic Factors and Healthcare Access - Alanazi, Manar Owayed; Aloufi, Nouf Ahmed; Alonezi, Sultanah Freah; Alahmri, Fahad Abdullah Mohmmed; Alenazi, Atlal Matar Hawi; Almutairi, Suad Saad; Alamri, Yasser Maanna Saleh; Alotaibi, Sami Abdullah Askar; Asiri, Sarah Ali; Alharbi, Alanood Sunitan (Journal of Ecohumanism, 2024)
The Healthcare industry is gradually emphasizing SDH interventions to eliminate differences in access to care and enhance population health. However, some of the parameters of social determinants top the list and major on the role of socioeconomic status in enhancing or worsening health. Nursing interventions in public health allow one to work with these factors, especially perinatal ones, in vulnerable populations by increasing access to and utilization of health services and enhancing health literacy. This review evaluates the evidence utilizing various nursing interventions in the attempt to eliminate barriers related to socioeconomic status in healthcare, specific to the outcomes and healthcare utilization among these patients, and more broadly, reduction of health disparities. This paper reviews literature and discusses major nursing interventions, issues, and recommendations for enhancing subsequent public health improvements.